The Role of Contemporary Teacher Education Institutions in Preparing Future Religious Teachers - Rosin, Nurhasfirah; Rekan, Abd. Aziz; Mohamed Adnan, Mohamad Azrien; Mohamad Salleh, Muhamad Nasir (Journal of Islamic Educational Research, 2024)
Malaysia is well-known for its diversity of ethnicity, cultures and religions, with Islam as the official religion at the federal level. In the context of Malaysia MADANI, education plays a crucial role, especially in maintaining the harmony of the country’s pluralistic society. Therefore, education continues to be empowered through modern teacher education institutes that train those in the teaching profession to produce individuals as agents to further the educational process. Educational institutions have existed for a long time and have developed through various institutions. Therefore, this writing aims to highlight the role played by the Academy of Islamic Studies, Universiti Malaya (APIUM) as a contemporary teacher education institution preparing prospective religious teachers who will lead education in this country. This study uses the literature review method involving content analysis of written materials such as academic journals, theses, books and so on. The results of the study prove that APIUM plays a significant role in providing quality future religious teachers and helping shape them as civic educators who will spread devotion and realize the aspirations of Malaysia MADANI.